NASYA-MOST VITAL THERAPEUTIC INTERVENTION OF PANCHAKARMA-A REVIEW - Divya S, *Zala; Dilip D, Prajapati; Anup B, Thakar; Nilesh N, Bhatt (International Journal of Ayurveda and Pharma Research, 2017)
Ayurveda is a Science and art of appropriate living which helps to achieve longevity. Panchakarma present a unique approach of Ayurveda to therapy with specially designed five procedures of internal purification of the body. One of the Panchakarma, the Nasyakarma is considered the best and the most specific procedure for disease of Urdhvajatrugatarogas like Pratishyay, Shirahshoola etc. It is also useful in other systemic diseases like Ardita, Kampavata. According to Ayurveda, the nose is the gate way to Shirah. So, systemically performed Nasyakarma cures almost all the diseases of Urdhvajatrugata rogas. Other procedures of Panchakarma are also very effective in numerous diseases according to condition but Nasya Karma is very easy to perform and there are no many strict regimens to follow during Nasya Karma but it will give effectual results in loads of diseases due to direct contact with nerve terminals by the nasal mucosa. So, it is demand of time to know about Nasyakarma and its importance. In this direction, to evaluate the actual efficacy of different Ayurveda treatment modalities; few works on Nasya Karma are compiled here. In current attempt, it has been planned to review as such works done on Nasyakarma. By this Present study it can be stated that in various diseases Nasya Karma is found to be significantly effective. It proved to be a better therapy as compared to only oral drug because it provides affect for longer duration than oral drug.